Teaching for critical thinking : tools and techniques to help students question their assumptions - Brookfield, Stephen (San Francisco : Jossey-Bass, 2012)
"In Teaching for Critical Thinking, Stephen Brookfield builds on his last three decades of experience running workshops and teaching courses on critical thinking to explore how student learn to think this way, and what teachers can do the help students develop this capacity. He outlines a basic protocol of critical thinking as a learning process that focuses on uncovering and checking assumptions, exploring alternative perspectives, and taking informed actions as a result. Written to address the broad range of disciplines, this book fosters a shared understanding of critical thinking and helps to various constituencies adapt general principles to specific disciplinary contexts"--
"In Teaching for Critical Thinking, Stephen Brookfield builds on his last three decades of experience running workshops and teaching courses on critical thinking to explore how student learn to think this way, and what teachers can do the help students develop this capacity. He outlines a basic protocol of critical thinking as a learning process that focuses on uncovering and checking assumptions, exploring alternative perspectives, and taking informed actions as a result. Written to address the broad range of disciplines, this book fosters a shared understanding of critical thinking and helps to various constituencies adapt general principles to specific disciplinary contexts"--
Includes bibliographical references (p. 261-268) and index.
Keywords: Critical thinking; Critical thinking -- Study and teaching; Psychology, Applied